Co-creation in partnerships contributing to the sustainability of food systems: insights from 52 case studies in Europe - de Vries, Hugo; Donner, Mechthild; Fabiano, Flavia; Mamès, Maurine; Lazaro-Mojica, Jonas; Cotillas, Eduardo; Avila, Concha; Martínez, Juan; Alcat, Gabriela; Rossi, Daniel; Pierantoni, Elisabetta; Marini, Tancredi; et al. (Frontiers in Sustainable Food Systems, 2024)
Institutions worldwide call for joint actions of multiple actors in partnerships to accelerate the transitions towards sustainable food systems and reach food security for everbody, allways. This requires insights into co-creating processes. Here, 52 European food system cases are analyzed. A methodology based on the game structure is used that permits standardizing data collection and extracting generic and cases-specific findings. Game building blocks correspond with key elements of co-creation processes, like defining mutually accepted objectives, engaging in types of activities, and efficient use of resources, boundary conditions, timings, and scales of operations. Results further indicate that different types of inclusive partnerships emerge, in which especially innovative private, including smallholders, and academic actors co-create value, all contributing to sustainability. The public and civil society actors emerge as important initiators, enablers, and organizers of scales of interaction, allowing generating snowball effects. Findings lead to an adapted concept for co-creating partnerships in food systems and recommendations for the European Partnership on sustainable food systems.